Independent directors, corporate ownership and cost of debt: Do politically connected independent directors matter? Evidence from China - Al-Delawi, Amjad S.; Harjan, Sinan A; Raewf, Manaf B; Thabit, Thabit H; Jameel, Alaa S (International Journal of Management and Sustainability, 2023)
This research seeks to determine whether politically connected independent directors (PCIDs) have a substantial effect in lowering the cost of debt (CoD). Therefore, the research aims to explain the relationship between political ties and the cost of debt, politically connected independent directors and the cost of debt, and state ownership and the relationship of politically connected independent directors and the cost of debt. In addition, we analyze the influence of corporate ownership on the connection. To illustrate this, we empirically study panel data which was separated into two periods (2011–2012 and 2013–2014) in state-owned and non-state-owned firms (SOEs and non-SOEs). We discovered that PCIDs had a considerable and unfavorable effect on the CoD, particularly in non-SOEs. As a result of the shared resource knowledge of PCIDs in government procurement contracts, finance, and law, the CoD in non-SOEs is reduced. The findings of this research add to the existing literature by employing data from China and demonstrating the impact of PCIDs in decreasing the cost of debt, particularly for non-SOEs.